Chromosome specific comparative genome hybridisation for determining the origin of intrachromosomal duplications - Griffin, D. K.; Sanoudou, D.; Adamski, E.; McGiffert, C.; O'Brien, P.; Wienberg, J.; Ferguson-Smith, M. A. (J Med GenetJ Med GenetJ Med Genet, 1998)
Chromosome specific comparative genome hybridisation (CGH) is a novel approach for the detection of cytogenetic abnormalities. It combines flow sorting of chromosomes, degenerate oligonucleotide primed (DOP)-PCR and a modified comparative genome hybridisation (CGH) technique to define the site and extent of intrachromosomal duplications. Chromosome specific paint probes for aberrant chromosomes and their normal homologues from four subjects with unbalanced duplications within chromosomes 2p11-15, 3q25-26, 5q34-qter, and 12q23-24.2 were made. They were then cohybridised on normal metaphase spreads and the ratio of their relative intensities of hybridisation analysed. The results were compared to those of similar experiments where regular CGH was performed on the same four patients. We provide evidence that this method can detect duplications and deficiencies which might be missed by conventional CGH, as the ratio of hybridisation of abnormal/normal DNA is 2:1 rather than 3:2. It is the method of choice where mosaicism is present or where only one of several homologous chromosomes is duplicated. Furthermore, it suggests that DOP-PCR amplifies all or most of the euchromatic regions of the genome equally.
Keywords: *Chromosome Aberrations/genetics; *Chromosome Disorders; Chromosomes, Human/*genetics; DNA Probes; Female; Flow Cytometry; Humans; Image Processing, Computer-Assisted; In Situ Hybridization, Fluorescence/*methods; Male; Polymerase Chain Reaction/methods